Strategies for enforcing shareholder rights in corporate governance in Nigeria (2014)
In spite of the legislative provisions on shareholder participation and involvement in the management of companies in Nigeria the practice is that shareholders are generally inactive, passive and generally disinterested in the management of their companies leaving the directors to have a free day. This paper examined the shareholder role in management in a developing corporate governance context, by critically analyzing the different procedures, legislative provisions and Codes of corporate governance available in order to strengthen and enhance proper shareholder contribution in corporate governance.